Computational model predicts protein binding sites of a luminescent ligand equipped with guanidiniocarbonyl-pyrrole groups - Rafieiolhosseini, Neda; Killa, Matthias; Neumann, Thorben; Tötsch, Niklas; Grad, Jean-Noël; Höing, Alexander; Dirksmeyer, Thies; Niemeyer, Jochen; Ottmann, Christian; Knauer, Shirley K.; Giese, Michael; Voskuhl, Jens; et al. (Beilstein Journal of Organic Chemistry, 2022)
The 14-3-3 protein family, one of the first discovered phosphoserine/phosphothreonine binding proteins, has attracted interest not only because of its important role in the cell regulatory processes but also due to its enormous number of interactions with other proteins. Here, we use a computational approach to predict the binding sites of the designed hybrid compound featuring aggregation-induced emission luminophores as a potential supramolecular ligand for 14-3-3ζ in the presence and absence of C-Raf peptides. Our results suggest that the area above and below the central pore of the dimeric 14-3-3ζ protein is the most probable binding site for the ligand. Moreover, we predict that the position of the ligand is sensitive to the presence of phosphorylated C-Raf peptides. With a series of experiments, we confirmed the computational prediction of two C2 related, dominating binding sites on 14-3-3ζ that may bind to two of the supramolecular ligand molecules.
Keywords: AIE luminophores; fluorescence emission; guanidiniocarbonyl-pyrrole; ligand binding; 14-3-3 protein

(untitled) - Aitken, A. (Plant Mol. Biol., 2002)

Seminars in Cell & Developmental Biology - Freeman, A. K.; Morrison, D. K. (14-3-3 Proteins: Diverse functions in cell proliferation and cancer progression, 2011)

(untitled) - Mhawech, P. (Cell Res., 2005)

(untitled) - Fu, H.; Subramanian, R. R.; Masters, S. C. (Annu. Rev. Pharmacol. Toxicol., 2000)

(untitled) - Kaplan, A.; Ottmann, C.; Fournier, A. E. (Pharmacol. Res., 2017)

(untitled) - Maity, D.; Gigante, A.; Sánchez-Murcia, P. A.; Sijbesma, E.; Li, M.; Bier, D.; Mosel, S.; Knauer, S.; Ottmann, C.; Schmuck, C. (Org. Biomol. Chem., 2019)

(untitled) - Milroy, L.-G.; Grossmann, T. N.; Hennig, S.; Brunsveld, L.; Ottmann, C. (Chem. Rev., 2014)

(untitled) - Vallet, C.; Aschmann, D.; Beuck, C.; Killa, M.; Meiners, A.; Mertel, M.; Ehlers, M.; Bayer, P.; Schmuck, C.; Giese, M.; Knauer, S. K. (Angew. Chem., Int. Ed., 2020)

(untitled) - Giese, M.; Niemeyer, J.; Voskuhl, J. (ChemPlusChem, 2020)

(untitled) - Schmuck, C.; Bickert, V. (J. Org. Chem., 2007)

(untitled) - Schug, K. A.; Lindner, W. (Chem. Rev., 2005)

(untitled) - Gigante, A.; Grad, J.-N.; Briels, J.; Bartel, M.; Hoffmann, D.; Ottmann, C.; Schmuck, C. (Chem. Commun., 2019)

(untitled) - Bartsch, L.; Bartel, M.; Gigante, A.; Iglesias‐Fernández, J.; Ruiz‐Blanco, Y. B.; Beuck, C.; Briels, J.; Toetsch, N.; Bayer, P.; Sanchez‐Garcia, E.; Ottmann, C.; Schmuck, C. (ChemBioChem, 2019)

(untitled) - Ehlers, M.; Grad, J.-N.; Mittal, S.; Bier, D.; Mertel, M.; Ohl, L.; Bartel, M.; Briels, J.; Heimann, M.; Ottmann, C.; Sanchez-Garcia, E.; Hoffmann, D.; et al. (ChemBioChem, 2018)

(untitled) - Mei, J.; Leung, N. L. C.; Kwok, R. T. K.; Lam, J. W. Y.; Tang, B. Z. (Chem. Rev., 2015)

(untitled) - Shi, H.; Liu, J.; Geng, J.; Tang, B. Z.; Liu, B. (J. Am. Chem. Soc., 2012)

(untitled) - Voskuhl, J.; Giese, M. (Aggregate, 2022)

(untitled) - Khan, I. M.; Niazi, S.; Iqbal Khan, M. K.; Pasha, I.; Mohsin, A.; Haider, J.; Iqbal, M. W.; Rehman, A.; Yue, L.; Wang, Z. (TrAC, Trends Anal. Chem., 2019)

(untitled) - Riebe, S.; Vallet, C.; van der Vight, F.; Gonzalez-Abradelo, D.; Wölper, C.; Strassert, C. A.; Jansen, G.; Knauer, S.; Voskuhl, J. (Chem. – Eur. J., 2017)

(untitled) - Molzan, M.; Kasper, S.; Röglin, L.; Skwarczynska, M.; Sassa, T.; Inoue, T.; Breitenbuecher, F.; Ohkanda, J.; Kato, N.; Schuler, M.; Ottmann, C. (ACS Chem. Biol., 2013)

(untitled) - Neale, C.; Hsu, J. C. Y.; Yip, C. M.; Pomès, R. (Biophys. J., 2014)

(untitled) - Romo, T. D.; Grossfield, A. (Biophys. J., 2014)

(untitled) - Nemec, M.; Hoffmann, D. (J. Chem. Theory Comput., 2017)

(untitled) - Eberhardt, J.; Santos-Martins, D.; Tillack, A. F.; Forli, S. (J. Chem. Inf. Model., 2021)

(untitled) - Trott, O.; Olson, A. J. (J. Comput. Chem., 2010)

(untitled) - Grad, J.-N.; Gigante, A.; Wilms, C.; Dybowski, J. N.; Ohl, L.; Ottmann, C.; Schmuck, C.; Hoffmann, D. (J. Chem. Inf. Model., 2018)

(untitled) - Dolinsky, T. J.; Nielsen, J. E.; McCammon, J. A.; Baker, N. A. (Nucleic Acids Res., 2004)

(untitled) - Dolinsky, T. J.; Czodrowski, P.; Li, H.; Nielsen, J. E.; Jensen, J. H.; Klebe, G.; Baker, N. A. (Nucleic Acids Res., 2007)

Analytical methods in supramolecular chemistry - Schalley, C. A. (Wiley-VCH, 2012)

(untitled) - O'Boyle, N. M.; Banck, M.; James, C. A.; Morley, C.; Vandermeersch, T.; Hutchison, G. R. (J. Cheminf., 2011)

(untitled) - Šali, A.; Blundell, T. L. (J. Mol. Biol., 1993)

(untitled) - Baker, N. A.; Sept, D.; Joseph, S.; Holst, M. J.; McCammon, J. A. (Proc. Natl. Acad. Sci. U. S. A., 2001)

(untitled) - Milchev, A.; Binder, K. (Macromolecules, 1996)

(untitled) - Underhill, P. T.; Doyle, P. S. (J. Non-Newtonian Fluid Mech., 2004)

(untitled) - Liu, B.; Wang, J.; Fan, X.; Kong, Y.; Gao, H. (J. Comput. Phys., 2008)

Computational soft matter: from synthetic polymers to proteins - Baschnagel, J.; Wittmer, J. P.; Meyer, H. (Monte Carlo Simulation of Polymers: Coarse-Grained Models, 2004)

(untitled) - Kirkpatrick, S.; Gelatt, C. D., Jr; Vecchi, M. P. (Science, 1983)

(untitled) - Černý, V. (J. Optim. Theory Appl., 1985)

Handbook of Metaheuristics. International Series in Operations Research & Management Science - Henderson, D.; Jacobson, S. H.; Johnson, A. W. (The theory and practice of simulated annealing, 2003)

(untitled) - Metropolis, N.; Rosenbluth, A. W.; Rosenbluth, M. N.; Teller, A. H.; Teller, E. (J. Chem. Phys., 1953)

(untitled) - Bezanson, J.; Edelman, A.; Karpinski, S.; Shah, V. B. (SIAM Rev., 2017)